Water Stress Differentially Modulates the Expression of Tomato Cell Wall Metabolism-Related Genes in Meloidogyne incognita Feeding Sites - Veronico, Pasqua; Rosso, Laura Cristina; Melillo, Maria Teresa; Fanelli, Elena; De Luca, Francesca; Ciancio, Aurelio; Colagiero, Mariantonietta; Pentimone, Isabella (Frontiers in Plant Science, 2022)
Microscopic observations and transcriptomic RNA-Seq analyses were applied to investigate the effect of water stress during the formation of tomato galls formation 1 and 2 weeks after inoculation with the root-knot nematode Meloidogyne incognita. Water stress affected root growth and the nematode ability to mount an efficient parasitism. The effects of water stress on the feeding site development were already observed at 1 week after nematode inoculation, with smaller giant cells, delayed development, and thinner cell walls. These features suggested changes in the expression levels of genes involved in the feeding site formation and maintenance. Gene Ontology (GO) enrichment and expression patterns were used to characterize differentially expressed genes. Water stress modified the expression profile of genes involved in the synthesis, degradation, and remodeling of the cell wall during the development of nematode feeding site. A comparison of gene expression with unstressed galls revealed that water stress intensified the up or downregulation of most genes. However, it particularly influenced the expression pattern of expansin A11 (Solyc04g081870.4.1), expansin-like B1(Solyc08g077910.3.1), a pectin acetylesterase (Solyc08g005800.4.1), and the pectin methylesterase pmeu1 (Solyc03g123630.4.1) which were upregulated in unstressed galls and repressed by water stress, at both sampling times. The expression of most members of the genes involved in cell wall metabolism, i.e., those coding for Csl, fasciclin, and COBRA proteins, were negatively influenced. Interestingly, alteration in the expression profiles of most dirigent protein genes (DIRs) and upregulation of five gene coding for Casparian strip domain protein (CASP)-like proteins were found. Gene expression analysis of galls from water stressed plants allowed us to better understand the molecular basis of M. incognita parasitism in tomato. Specific genes, including those involved in regulation of cellulose synthesis and lignification process, require further study to develop defense strategies against root-knot nematodes.